Place of Orthopedic Treatment in the Talus Fractures: About Two Cases - Elbahraouy, A.; Elyaakoubi, T.; Zaizi, A.; Bouabid, S.; Boussouga, M. (International Journal of Innovative Research in Medical Science, 2020)
Fractures of the talus are rare and serious injuries. Their prognosis is bad since they are complicated in most cases of osteonecrosis of the talus; they require adequate treatment either surgical or orthopedic whose aim is to minimize the risk of osteonecrosis and osteoarthritis; the authors report two cases of fracture of the talus treated conservatively with good clinical and radiological outcome two years of decline.